Progressive pulmonary fibrosis in myositis-specific antibody-positive interstitial pneumonia: a retrospective cohort study - Wang, Huijuan; Wang, Yuanying; Sun, Di; Yu, Shiwen; Du, Xuqin; Ye, Qiao (Frontiers in Medicine, 2024)
Objectives Idiopathic inflammatory myopathy (IIM) frequently coexists with interstitial pneumonia (IP) and is commonly the initial or sole manifestation accompanied by positive myositis-specific autoantibodies (MSAs), even in the absence of meeting diagnostic criteria. This study aims to evaluate the proportion of progressive pulmonary fibrosis (PPF) and identify potential predictors influencing the progression of pulmonary fibrosis in patients with MSA-IP. Methods This descriptive study employed a retrospective cohort design, enrolling patients diagnosed with interstitial pneumonia and positive MSAs at Beijing Chao-Yang Hospital in a sequential manner. Clinical data were systematically collected from the patients’ medical records during regular follow-up visits conducted every 3 to 6 months. Cox regression analysis was utilized to identify independent predictors of PPF in patients with positive MSAs and interstitial pneumonia. Results A total of 307 patients were included in the study, with 30.6% of them developing PPF during a median follow-up period of 22 months. Kaplan–Meier survival curves demonstrated a significantly lower survival in the PPF patients compared to the non-PPF patients (median 11.6 months vs. 31 months, p = 0.000). An acute/subacute onset of interstitial pneumonia (HR 3.231, 95%CI 1.936–5.392, p = 0.000), lower diffusing capacity of the lungs for carbon monoxide (DLCO) % predicted (HR 6.435, 95%CI 4.072–10.017, p = 0.001), and the presence of diffuse alveolar damage (DAD) on high-resolution computed tomography (HRCT) (HR 8.679, 95%CI 1.974–38.157, p = 0.004) emerged as independent predictors of PPF. Notably, the implementation of triple therapy comprising glucocorticoids, immunosuppressants, and antifibrotic drugs was associated with a reduced risk of developing PPF (HR 0.322, 95%CI 0.115–0.899, p = 0.031). Conclusion Approximately 30.6% of patients with MSA-IP may develop PPF within the follow-up period. Patients presenting with an acute/subacute onset of interstitial pneumonia, lower predicted DLCO SB% and evidence of DAD on HRCT are more susceptible to developing PPF. Conversely, the administration of triple therapy appears to serve as a protective factor against the development of PPF in patients with MSA-IP.